Factors Affecting Decisions To Choose Application Based Transportation - Nur Elfi Husda; Nuramaliafitrah . (Jurnal Manajemen Indonesia, 2020)
The existence of service application for ojek and call taxi is a solution for people who have difficulty using public transport due to its accessibility and point to point pick up service. This study aims to determine the factors that influence customer decisions in using application-based “Motorbike Taxi” like Go-Jek. This research was conducted on the Putera Batam University’s students that have used Go-Jek application, with a sample size of 100 students as its respondents. The sampling technique used is incidental sampling method and is estimated to represent the population. Data analysis method used in this research is descriptively quantitative analysis of the factors that influence students in using the services of Go-Jek. The results showed that service quality factors that influence students’ decisions to choose transportation services based on “Motorbike Taxi” service orders consist of 6 factors: service, completeness of driving, security, trust, responsiveness and reliability, where the most dominant factor is service factor. Keywords: Application-based transportation, service quality, customer decisions